Pet-sensitive design a study on the integration of companion animals in residential developments in Davao City - Baldonado, Arielle Jan S.; Juanga, Jean Marie V. (2016)
There is an increasing number of pet owners, yet the available space is dwindling. This poses a challenge to pet owners in acquiring their own houses. This also limits pet ownership, which may result to pet abandonment or poor fostering and adoption rates. This can be observed more clearly in condominium development. Majority impose rules on pet ownership, limiting the number, breed, and size of the animals that may be kept as pets. The ideal living condition for companion animals and humans in residential development was determined through a preferential survey on 382 pet owners in Davao City. It was found out that a subdivision type of development is acceptable to 77.27% of pet owners, more than that of residential condominium (54.90%). The relationship between human and companion animals is a strong familial bond as most pet owners see their pets as part of their family, preferring to share spaces of the house with them. While majority of pet owners have dogs, it is usually them who are affected by regulations when owning or renting estate properties. There is a need to include companion animals as design considerations in residential developments to tap the growing market of pet owners.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.